Validity and Reliability of the Maritime English Seafarer Proficiency Exam - Gumay, Adesvan; Herningsih, Siwi Woro; Viamita, Evi Sukma (Jurnal Ekonomi, 2024)
The purpose of this study is to determine the Validity and Reliability of the Maritime English Seafarer Expertise Exam conducted by PUKP 02 Banten and Surrounding Areas where the exam is held at the Banten shipping Polytechnic campus and questions are given in the form of multiple choice. This study is categorized as a descriptive analysis because it is intended to describe the level of difficulty, discriminating power, validity and reliability of the Maritime English test for level III cadets at the Sailing School for the 2019/2020 school year by analyzing the validity and reliability of each item. The results of this study concluded: 1) The validity of the seafarer expertise exam questions majoring in nautics there are 43 question items or equivalent to 71.66% of the total items are said to be valid, so the test has good validity because the value of the correlation / coefficient relationship is greater (>) than table (Rtable) = 0.1071 for a significance level of 5%. For the Engineering Department there are 41 question items or equivalent to 68.33% of the total items are said to be valid, so the test has good validity because the value of the correlation / coefficient relationship is greater (>) than the table (Rtable) = 0.2483 for a significance level of 5%. 2) The reliability of the nautical department test device was found to be 0.5968 while for the engineering department of 0.6789 the figure was in the interval 0.40 to 0.70 with moderate interpretation. Thus it can be concluded that the Maritime English sailor skill test has sufficient reliability.